On Schmid & Endicott’s Mariposas de Venezuela. / Sobre Mariposas de Venezuela, de Schmid & Endicott. - Viloria, Ángel L.; Rivas, Gilson A.; González, Jorge M. (Anartia, 2020)
RESUMEN We have recently learned that Dr. Michael Schmid (1948-2018) (Fig. 1), biologist and notable cytogeneticist, passed away in Würzburg, Germany (Höhn 2018). One of us (GAR) was honored and distinguished by his professional collaboration in the field of amphibian systematics and cytogenetics (see Kaiser et al. 2015), a scientific field to which he made great contributions. For instance, two monographs on phylogenetics, cytogenetics and natural history in terraranan and hemiphractid frogs (Schmid et al. 2010, 2012), and some more specific works on reptilian and amphibian taxa from northern Venezuela, especially dendrobatid and direct-developing frogs (Schmid et al. 1992, 2002, 2003, Manzanilla et al. 1996, Kaiser et al. 2003), and geckos or the genus Gonatodes, a group of lizards that he considered very promising for cytogenetic research (pers. comm. to GAR, 16 April 2015).